A histology-free description of Tetrastemma cupido sp. nov. (Nemertea: Eumonostilfera) from Sagami Bay, Japan. Issue 5 (3rd July 2021) - Hookabe, Natsumi; Kohtsuka, Hisanori; Kajihara, Hiroshi
ABSTRACT: We provide a histology-free description of the eumonostiliferous hoplonemertean Tetrastemma cupido sp. nov. based on specimens collected subtidally at a depth of 100 m in Sagami Bay, Japan. In T. cupido sp. nov., the ocelli are arranged in two, anterior and posterior, pairs of clusters, each consisting of up to eight and four ocelli, respectively. This feature is unique to T . cupido sp. nov. among ∼110 congeners in the genus Tetrastemma Ehrenberg, 1828, where the ocelli are unexceptionally four in number. The generic affiliation of the new species was confirmed with a molecular phylogenetic analysis based on partial sequences of cytochrome c oxidase subunit I, 16S rRNA, 18S rRNA and 28S rRNA genes among 31 species of eumonostiliferans. In the resulting tree, T. cupido sp. nov. was nested in a clade comprised of 11 species of Tetrastemma including the type species Tetrastemma flavidum Ehrenberg, 1828 . Tetrastemma cupido sp. nov. is morphologically similar to Amphiporus superbus (Girard in Stimpson W. 1854. Marine Invertebrata of Grand Manan. Smithsonian Contr Knowl. 6:5–67), but can be distinguished from the latter by having a mid-dorsal white stripe. Publication LSID: lsid:zoobank.org:pub:C58863AC-6176-453C-94EA-BD79D413EF41